2008
DOI: 10.1590/s0102-311x2008001200011
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic infection in family contacts of patients with human visceral leishmaniasis in Três Lagoas, Mato Grosso do Sul State, Brazil

Abstract: The Brazilian city of Três Lagoas, Mato Grosso do Sul State, has experienced an urban outbreak of visceral leishmaniasis since 2000. In 2002, due to the increase in the number of cases, 46 families with cases of visceral leishmaniasis were studied to verify the prevalence of asymptomatic infection in household contacts. Indirect immunofluorescence and ELISA showed a 36.4% positive infection rate. There were no cases of symptomatic disease among these contacts. There was no statistically significant difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…In Nascimento et al 8 , individuals under 15 years of age in the county of São José de Ribamar showed a prevalence of 61.7% by MST and 19.7% by ELISA. Oliveira et al 12 , in Três Lagoas, Minas Gerais State, with participants of all ages, showed a 36.4% positive rate by ELISA. The higher infection rate detected by MST in the current study may be explained by the fact that it included family members and neighbors of the index case rather than the general population.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In Nascimento et al 8 , individuals under 15 years of age in the county of São José de Ribamar showed a prevalence of 61.7% by MST and 19.7% by ELISA. Oliveira et al 12 , in Três Lagoas, Minas Gerais State, with participants of all ages, showed a 36.4% positive rate by ELISA. The higher infection rate detected by MST in the current study may be explained by the fact that it included family members and neighbors of the index case rather than the general population.…”
Section: Discussionmentioning
confidence: 93%
“…Asymptomatic infection is the most common clinical form in endemic areas and is normally associated with the presence of a case of classic VL in the family or neighborhood, suggesting that these individuals are subject to similar risk of infection, since they have similar socioeconomic and environmental conditions and habits 10,11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Entre os pacientes estudados, observou-se predomínio da doença no sexo masculino (74,5%), o que está de acordo com outros autores 10,16 que justificam o fato pela presença destes em áreas que oferecem maior risco, por moradia, trabalho ou lazer, porém, sabe-se que a infecção pode ocorrer de forma igual, sem preferência por sexo 17 . A possível associação dessa susceptibilidade masculina a fatores genéticos já foi comentada em um estudo realizado no Piauí, embora as causas ainda não tenham sido devidamente esclarecidas 18 .…”
Section: Métodos Resultadosunclassified
“…According to Oliveira et al (2008) and Lindoso et al (2006) the main factors that contribute to the increased lethality are the late diagnosis and the expansion of the disease affecting patients with comorbidities, with infectious and haemorrhagic complications as the main risk factors for death in VL. In this study, 12 individuals showed an HIV-VL co-infection, which increases lethality.…”
Section: Discussionmentioning
confidence: 99%